2021
DOI: 10.1108/mip-01-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

How nostalgia forges place attachment and revisit intention: a moderated mediation model

Abstract: PurposeAnalyzing sport fans' emotions has attracted much attention and offered important implications for research on sport consumer behavior. As such, diverse emotional factors have been considered to understand their behavioral responses. However, the concept of nostalgia has been examined to a lesser extent in the context of sport. Thus, this study investigated the role of nostalgia and its relationships with place attachment and revisit intention. The frequency of past experience was used as a moderator in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 68 publications
1
35
0
1
Order By: Relevance
“…Second, the perception of COVID‐19 has significantly affected consumers' psychological and emotional states. Therefore, future studies may consider more variables that can influence consumers' consumption patterns, such as nostalgia (Cho, 2021; Cho et al, 2020; Cho, Chiu, et al, 2021; Cho, Joo, et al, 2019; Cho, Khoo, et al, 2019; Cho, Lee, et al, 2021), anxiety (Lee, 2020), and stress (Taylor et al, 2020), to explore their impacts on purchase behavior. Third, as the income level was found to be the moderator in this study, other factors, such as age, online/offline consumption, and knowledge levels about vaccinations may be taken into consideration for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the perception of COVID‐19 has significantly affected consumers' psychological and emotional states. Therefore, future studies may consider more variables that can influence consumers' consumption patterns, such as nostalgia (Cho, 2021; Cho et al, 2020; Cho, Chiu, et al, 2021; Cho, Joo, et al, 2019; Cho, Khoo, et al, 2019; Cho, Lee, et al, 2021), anxiety (Lee, 2020), and stress (Taylor et al, 2020), to explore their impacts on purchase behavior. Third, as the income level was found to be the moderator in this study, other factors, such as age, online/offline consumption, and knowledge levels about vaccinations may be taken into consideration for future research.…”
Section: Discussionmentioning
confidence: 99%
“…and emotional states. Therefore, future studies may consider more variables that can influence consumers' consumption patterns, such as nostalgia (Cho, 2021;Cho et al, 2020;Cho, Joo, et al, 2019;Cho, Khoo, et al, 2019;Cho, Lee, et al, 2021), anxiety (Lee, 2020), and stress (Taylor et al, 2020), to explore their impacts on purchase behavior. Third, as the income level was found to be the mod- The findings of this study contribute to a better comprehension of how COVID-19 triggers consumer impulse buying behavior through fearful emotion and how income level moderates the influence of fear on impulse buying behavior.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…These studies reported that nostalgia's effect on revisit intention was statistically supported for baseball fans in South Korea (e.g. Cho, 2021). Meanwhile, the effect was rejected for football fans in Singapore (e.g.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Similarly, Cho et al (2019) noted that desire could play a mediating role in the relationship between personal factors and behavioral outcomes in a spectator sport, which is consistent with the environmental psychology behavioral model (Mehrabian and Russell, 1974). Given that sports spectatorship and sport tourism are emotional experiences (Cho, 2021;Cho et al, , 2020aCho et al, , b, 2021Joo et al, 2020), the model of goal-directed behavior would be more appropriate in explaining sport tourists' behavioral intention than just the theory of planned behavior, and this led to the following hypotheses:…”
Section: Theory Of Planned Behavior and Model Of Goal-directed Behaviormentioning
confidence: 99%